Fabrication and characterization of a miniaturized planar voltammetric sensor array for use in an electronic tongue - Twomey, K.; Alvarez De Eulate, Eva; Alderman, J.; Arrigan, Damien (MDPI Publishing, 2009)
A planar voltammetric sensor array for use in an electronic tongue was fabricated using a combinationof microfabrication techniques. The techniques of e-beam evaporation and pulsed laser deposition wereapplied to prepare a device that contained all of the electrodes integrated on a silicon die (6mm×6 mm).The working electrodes were metals gold, platinum, iridium and rhodium. They were characterized bySEM and EDX, and by electrochemical investigation of the packaged dies with cyclic voltammetry insolutions of sulfuric acid and of ferrocene carboxylic acid in aqueous buffer solution. The robustness andreproducibility of the devices were assessed by potential cycling in acid solution.